Cultural fit in emotion versus language: a study of Dutch-speaking Belgians and Turkish migrants in Belgium - Rüya Su Şencan; Batja Mesquita; Katie Hoemann; Katie Hoemann (Frontiers in Psychology)
Cultural fit is thought to benefit immigrants’ wellbeing and integration. Previous research on cultural fit focused on explicit attitudes (e.g., how individuals identify with their heritage and host cultures) at the expense of psychological processes (e.g., the extent to which individuals make meaning in similar ways with their surrounding culture). We examined cultural fit in meaning-making in emotional contexts in two complementary ways: first, based on patterns of emotion endorsement (emotional fit), second, based on patterns of word use describing emotional situations (language fit). Dutch-speaking Belgians and Turkish migrants in Belgium (Ns = 100) described two positive and two negative emotional situations, and rated the intensity of their experience on a set of emotion terms. Language patterns in the descriptions, as quantified by the Linguistic Inquiry and Word Count, distinguished between cultures more effectively than rating patterns. The two fit measures did not converge; they were in fact negatively associated in some analyses, particularly for Turkish migrants’ emotional fit and language fit with Belgian culture, suggesting that when these migrants felt similar emotions, they attended to different aspects of their experience. Future research should disentangle the implications of various types of cultural fit on outcomes relevant to immigrant minorities.